2011
DOI: 10.1186/1476-511x-10-156
|View full text |Cite
|
Sign up to set email alerts
|

The role of common variants of the cholesteryl ester transfer protein gene in left main coronary artery disease

Abstract: BackgroundThe cholesteryl ester transfer protein (CETP) has a central role in the lipid metabolism and therefore may alter the susceptibility to atherosclerosis.MethodsThe DNA of 471 subjects [133 subjects with angiographically documented left main coronary artery disease (LMCAD), 241 subjects with more peripheral coronary artery disease (MPCAD) and 97 subjects self reported healthy (Controls)] was analyzed for the frequency of TaqIB and I405V polymorphisms in the gene coding CETP.ResultsThere is no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
1
25
0
2
Order By: Relevance
“…It is currently believed that CHD is caused by multiple genetic factors combined with environmental factors (Tsujita et al, 2007;Kimura, 2009), and that lipid metabolism disorder can lead to the occurrence of CHD (Kolovou et al, 2011). The present study demonstrated that the plasma levels of TC, LDL-C, and lipoprotein(a) were significantly higher in the ACS and stable CHD groups compared to the control group.…”
Section: Discussionsupporting
confidence: 58%
“…It is currently believed that CHD is caused by multiple genetic factors combined with environmental factors (Tsujita et al, 2007;Kimura, 2009), and that lipid metabolism disorder can lead to the occurrence of CHD (Kolovou et al, 2011). The present study demonstrated that the plasma levels of TC, LDL-C, and lipoprotein(a) were significantly higher in the ACS and stable CHD groups compared to the control group.…”
Section: Discussionsupporting
confidence: 58%
“…The study selection process is detailed in Figure 1 . Through a comprehensive retrieval and evaluation, 45 studies from 44 papers with 20,866 cases and 21,298 controls met the inclusion criteria to assess the association between the CETP TaqIB polymorphism and the composite ischemic CVD [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. The selected study characteristics and data are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In consideration of the study design, 6 studies were prospective [ 20 , 40 , 43 , 45 , 49 ] and the remaining 41 studies were retrospective [ 11 , 17 , 21 , 22 , 36 - 38 , 41 , 42 , 44 , 46 - 48 , 50 - 67 ]. In addition,11 of the 47 studies were P-B [ 20 - 22 , 36 , 37 , 40 , 43 , 46 , 49 , 54 ] and the remaining studies were H-B [ 11 , 17 , 38 , 39 , 41 , 42 , 44 , 45 , 47 , 48 , 50 - 53 , 55 - 66 ]. CAD was regarded as the main outcome in most of the studies [ 11 , 17 , 21 , 22 , 36 - 40 , 42 , 44 , 45 , 47 , 49 - 51 , 53 , 55 - 61 , 64 - 66 ], except 8 studies analyzed MI [ 20 , 43 , 46 , 48 , 52 , 54 , 62 , 63 ] and 2 studies analyzed ACS [ …”
Section: Resultsmentioning
confidence: 99%
“…In addition,11 of the 47 studies were P-B [ 20 - 22 , 36 , 37 , 40 , 43 , 46 , 49 , 54 ] and the remaining studies were H-B [ 11 , 17 , 38 , 39 , 41 , 42 , 44 , 45 , 47 , 48 , 50 - 53 , 55 - 66 ]. CAD was regarded as the main outcome in most of the studies [ 11 , 17 , 21 , 22 , 36 - 40 , 42 , 44 , 45 , 47 , 49 - 51 , 53 , 55 - 61 , 64 - 66 ], except 8 studies analyzed MI [ 20 , 43 , 46 , 48 , 52 , 54 , 62 , 63 ] and 2 studies analyzed ACS [ 41 ] as the endpoint. A significant departure from HWE was found in 7 studies [ 21 , 39 , 48 , 52 , 63 ].…”
Section: Resultsmentioning
confidence: 99%